Physics Applied to the Sailboat Optimum Upwind Path Algorithm - ., Caden Ashmore; Dr. Dipti Sharma (Engineering And Technology Journal, 2024)
Autonomous vehicles are predicted to be an enormous disrupter to our economy, creating a massive and unpredictable impact, much like the smartphone on telecommunications. Marine transportation is at the leading edge, with automated boats crossing the oceans. Sailboats and sail-assisted boats, in particular, are not just efficient and environmentally friendly, but also allow automated boats to be at sea for extended periods. This is excellent for applications such as oil and gas pipeline monitoring, data collection, and ocean mapping. Navigation is critical, however, one issue unique to sailboats is that it is impossible to sail directly into the wind. In order to navigate upwind the boat needs to follow a zig-zag route towards the destination. Details such as the angles, lengths, and number of zig-zags are critical to maximizing forward progress to the destination. This research includes an approach to determine the optimal zig-zag route for efficiency, which could be used as part of route planning before a journey begins, or as part of an autonomous sailboat system.